Extraction of starch, xylose and glucose from oil palm trunk for bioethanol production - Wong, Lih Jiun (2019)
Use of oil palm trunk as sugars resource of biomass is currently under intensive study as an alternative growth substrate for bio-based chemical an energy production. It will benefit the environmental and reduce the agricultural waste. The complexity of chemical compositions in lignocelluloses as inhibits in degradation of lignin, hemicelluloses and cellulose which contain starch, five-and six-carbon sugars; prior to hydrolyzed and followed by co-fermentation for bioethanol production. Generally, this study aims to optimize the extraction of starch and mixed xylose-glucose from oil palm trunk and co-fermentation process of mixed sugars to bioethanol. Chemical analysis was carried out based on TAPPI Test Methods (TAPPI, 2000) in determination of the chemical compositions of different levels and different portions of OPT. Low lignin and hemicelluloses and cellulose were found in this batch of study. It shows that OPT contains considerable extractives content which is valuable be source of chemical value added products like fermentable sugars. For the study 2 (Starch extraction by Distilled Water and Chemical from OPT), starch in the oil palm trunk was extracted by 0.2 % sodium metabsisulphite (w/v) and 0.5 % lactic acid (v/v), and aqueous water respectively treated with levels of temperatures and times. Value P≤0.01 significance was observed for the main effects (temperature and time) on the starch yield with water solution and chemicals. A significant interaction was also found between two main effects (temperature and time). 19.7 % of starch yield was obtained by distilled water at 50 °C, 1 h, whereas 14.0 % of starch was obtained by chemicals at 26 ± 2 °C, 1 h). From the Response Surface Methodology (RSM) optimization analysis, optimum starch yield 12.8 % was extracted by room temperature 26 ± 2 °C and 1 h by chemical solution. Whereas, from the RSM optimization analysis, optimum starch yield 16.3 % was extracted by distilled water under parameter 50 °C and 1 h. From the findings for study 2, the optimum starch yield can be obtained in lower temperature when OPT powder treated with chemicals solution than aqueous water. Continuous dilute acid hydrolysis and simultaneous acid hydrolysis (115 °C, 120 °C and 130 °C reacted with 15 min, 30 min and 60 min) for producing xylose and glucose. 2 %, 4 % and 6 % of acid sulphuric was used for hydrolysis process. For continuous acid hydrolysis, optimum parameter of starch extraction method parameter (0.2 % sodium metabsisulphite (w/v) and 0.5 % lactic acid (v/v), 26 ± 2 ˚C and 1 h), the extracted starch was mixed with residue of oil palm trunk powder for dilute acid hydrolysis process. Simultaneous acid hydrolysis used untreated raw OPT powder for glucose and xylose production. The higher glucose yield occurred at dilute acid hydrolysis with the parameter of 6 % sulphuric acid concentration reacted for 60 min on 60 mesh of OPT powders at 100 °C with a total glucose yield of approximately 15.3 % by simultaneous hydrolysis. The optimum xylose yield occurred with the parameter of 2 % sulphuric acid concentration reacted for 30 min on 60 mesh of OPT powders at 115 °C with a total xylose yield of approximately 32.4 % by continuous acid hydrolysis. Value P≤0.01 significance was observed for the main effects (acid concentration, temperature and time). By RSM analysis, optimum glucose and xylose can be obtained by conducting continuous hydrolysis temperature 130 °C for 53 min with 2 % acid concentration. Conclusively, the total yield of glucose-xylose was improved and approximately range of 2.5 % - 28.8 % higher than total glucose-xylose yield from untreated OPT powder. Co-fermentation of glucose and xylose to bioethanol was carried out using engineered strains of Saccharomyces cerevisiae 424A(LNH‐ST) and E.coli strain B, respectively. There was a preferential order of sugar utilization: first using glucose followed by xylose. Generally, the optimum ethanol yield of 85.41 % using yeast as fermentation microbes was obtained at temperature 30 °C, pH 4. While, the optimum ethanol yield obtained from E.coli strain B was 86.01 % at temperature 34 °C, pH 6. Value P≤0.0001 significance was observed for the main effects (pH and temperature). From the optimization analysis, 87.9 % of ethanol conversion yield can be obtained by conducting the fermentation at temperature 34 °C and pH 6 by E.coli strain B; whereas 82.1 % of ethanol conversion yield can be obtained at 30 °C and pH 4 by S.cerevisiae 424A(LNH-ST). Generally, Oil palm trunk contains considerable amount of extractives and lower lignin which suitable for starch and sugars extraction especially glucose and xylose and potentially be one of the biomass resource energy in bioethanol production.